Chất lượng dịch vụ, sự hài lòng và lòng trung thành của khách hàng đối với dịch vụ internet băng thông rộng của VNPT An Giang - Nguyễn Văn, Sĩ; Nguyễn Viết, Bằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study aims to examine the linkages among service quality, customer satisfaction, and customer loyalty toward broadband Internet service of Vietnam Posts and Telecomunication Group (VNPT) in An Giang province. It uses both qualitative and quantitative approaches through focus group discussion and face-to-face interviews with 285 customers respectively. The results indicate that: (i) Service quality and satisfaction affect customer loyalty; (ii) Service quality impacts customer satisfaction; and (iii) Service quality is influenced by five determinants including reliability, responsiveness, assurance, tangibility, and empathy.